2021
DOI: 10.1021/acs.jpcc.1c04092
|View full text |Cite
|
Sign up to set email alerts
|

Size Effect on the Reaction Rate of Surface Nanodroplets

Abstract: Compartmentalizing reagents within small droplets is promising for highly efficient conversion and simplified procedures in many biphasic chemical reactions. In this work, surface nanodroplets (i.e., less than 100 nm in their maximal height) were employed to quantitatively understand the size effect on the chemical reaction rate of droplets. In our systems, a surface-active reactant in pure or binary nanodroplets reacted with the reactant in the bulk flow. Meanwhile, the product was removed from the droplet su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Such results are consistent with that reported by Wang et al, who also found that the reaction rate of the manganese-catalyzed oxidation of SO 2 increased with a decreasing droplet diameter and an increasing S/V. The enhancing effect of bigger S/V on the reaction rate could be attributed to the stronger electric field on the surface, which can lower the activation energy of the reaction and enhance the mass transport of reagents and products through the aerosol/air interface. …”
Section: Resultssupporting
confidence: 92%
“…Such results are consistent with that reported by Wang et al, who also found that the reaction rate of the manganese-catalyzed oxidation of SO 2 increased with a decreasing droplet diameter and an increasing S/V. The enhancing effect of bigger S/V on the reaction rate could be attributed to the stronger electric field on the surface, which can lower the activation energy of the reaction and enhance the mass transport of reagents and products through the aerosol/air interface. …”
Section: Resultssupporting
confidence: 92%
“…Table 3 The enhanced reaction rate in smaller droplets was also found and quantitatively analyzed in our previous results. 30,35 The accelerated bubble kinetics in smaller droplets was attributed to the faster accumulation of the hydrogen product in smaller droplets with a higher surface-to-volume ratio.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The mass flux between the droplets into the surrounding phase also plays an important role in the droplet reaction kinetics. , In this regard, femtoliter droplets immobilized on a solid surface have been used as a model system for the quantitative study of droplet reaction rates. Because the three-phase contact line of surface droplets is pinned by the solid surface, these droplets are stable on the substrate as the reactant is supplied in a controlled flow. The volume of surface droplets is conveniently controlled by the solvent exchange method .…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced reaction rate in smaller droplets was also found and quantitatively analyzed in our previous results. 28,36 The accelerated bubble kinetics in smaller droplets was attributed to the faster accumulation of the hydrogen product in smaller droplets with a higher surface-to-volume ratio.…”
Section: Growing Microbubbles In Reacting Surface Dropletmentioning
confidence: 99%
“…The mass flux between the droplets to the surrounding phase also plays an important role in the droplet reaction kinetics. 27,28 In this regard, femtoliter droplets immobilized on a solid surface have been used as a model system for the quantitative study of droplet reaction rates. As the three-phase contact line of surface droplets is pinned by the solid surface, these droplets are stable on the substrate as the reactant is supplied in a controlled flow.…”
Section: Introductionmentioning
confidence: 99%